Nanoemulsions of sulfonamide carbonic anhydrase inhibitors strongly inhibit the growth of Trypanosoma cruzi - Alane Beatriz Vermelho; Verônica da Silva Cardoso; Eduardo Ricci Junior; Elisabete Pereira dos Santos; Claudiu T. Supuran (Taylor & Francis Group, 2018)
Sulfonamide carbonic anhydrase (CA, EC 4.2.1.1) inhibitors targeting the α-class enzyme from the protozoan pathogen Trypanosoma cruzi, responsible of Chagas disease, were recently reported. Although many such derivatives showed low nanomolar activity in vitro, they were inefficient anti-T. cruzi agents in vivo. Here, we show that by formulating such sulfonamides as nanoemulsions in clove (Eugenia caryophyllus) oil, highly efficient anti-protozoan effects are observed against two different strains of T. cruzi. These effects are probably due to an enhanced permeation of the enzyme inhibitor through the nanoemulsion formulation, interfering in this way with the life cycle of the pathogen either by inhibiting pH regulation or carboxylating reactions in which bicarbonate/CO2 are involved. This type of formulation of sulfonamides with T. cruzi CA inhibitory effects may lead to novel therapeutic approaches against this orphan disease.